Implementasi Etika Bisnis Islam pada Pemasaran Marketplace Shopee - Yudha Nur Imron; Ely Masykuroh (Institut Agama Islam Negeri Ponorogo, 2023)
This field of qualitative research aims to examine global Islamic online marketing strategies on Shopee. This study used data mining methods for examination, classification, verification, analysis, and conclusion. The research found that Shopee's strike price system for online selling and buying follows the Islamic business ethics axiom of unity ethics and free will. Marketing does not discriminate, and he has tried to boost sales as a businessman. Sellers play a drastic price game by raising the price before the strike price. That can hurt other markets and consumers. Online marketing using a promotional system to buy and sell on Shopee Marketplace does not violate the ethical principles of unity and free will. The promotion is not coercive because it applies to all consumers. It has reduced losses on its Shopee Marketplace products. Balance, accountability, and truth are incompatible with Islamic business ethics because this marketing relies on positive testimonials from consumers or delivery couriers. The Shopee marketplace's quality system of goods conforms to the ethical hypothesis of unity and free will because sellers use some goods for bonus systems or strike prices to reduce losses for all consumers such as violates balance, accountability, and truth because the product is nearly expired and doesn't match the promotion's description.